2021
DOI: 10.3389/fgene.2021.775006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Hub Genes and miRNA-mRNA Pairs Related to the Progression and Prognosis of Cervical Cancer Through Integrated Bioinformatics Analysis

Abstract: In recent years, the incidence and mortality of cervical cancer have increased worldwide. At the same time, increasing data have confirmed that miRNA-mRNA plays a positive or negative regulatory role in many cancers. This study attempted to screen effective miRNA-mRNA in the progression of cervical cancer, and to study the mechanism of miRNA-mRNA in the progression of cervical cancer. The expression profile data of GSE7410, GSE 63514, GSE 86100 and TCGA-CESC were downloaded, and 34 overlapping differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The interaction between BLM and EZH2 reportedly affects the occurrence and development of prostate cancer [ 9 ]. IQGAP3 promotes tumor migration and invasion in the ovarian and gastric cancers [ 10 , 11 ] Inhibiting TYMS promotes the proliferation, migration, and invasion of the cervix [ 12 ]. Additionally, KM survival analysis identified the gene with potential prognostic value, DIAPH3 .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between BLM and EZH2 reportedly affects the occurrence and development of prostate cancer [ 9 ]. IQGAP3 promotes tumor migration and invasion in the ovarian and gastric cancers [ 10 , 11 ] Inhibiting TYMS promotes the proliferation, migration, and invasion of the cervix [ 12 ]. Additionally, KM survival analysis identified the gene with potential prognostic value, DIAPH3 .…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [18] reported the up-regulation of TYMS in breast cancer tissue, and the increased TYMS promoted cell proliferation of breast cancer and colorectal cancer by accelerating the cell cycle progress [19,20]. However, Mingxu Fu et al [21] found promoted proliferation, migration, invasion and reduced cell apoptosis in TYMS-knockdown HeLa cells, and TYMS plays the role of a tumour suppressor gene in cervical cancer. These reveal the differences of TYMS expression and functions in different types of tumors.…”
Section: Discussionmentioning
confidence: 99%